2004
DOI: 10.1007/s11095-004-7670-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polymer-Drug Conjugates with High Drug Payload for Enhanced Cellular Delivery

Abstract: Purpose. To synthesize and evaluate hyperbranched polymer (HBP)-drug conjugates with high drug payload for enhanced cellular delivery. Methods. Polyol-and polyglycerol-ibuprofen conjugates with or without imaging agent fluorescein isothiocyanate (FITC) were synthesized using dicyclohexilcarbodiimide (DCC) as a coupling agent. Drug-polymer conjugates were characterized using 13 C NMR, 1 H NMR, and gel permeation chromatography (GPC). Stability of the drug-conjugates was studied using free drug release through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 33 publications
5
132
0
Order By: Relevance
“…Concerning the charging state of ibuprofen at different pH conditions, it has been found that at high pH conditions (pH > 10.5), ibuprofen becomes fully ionized (due to deprotonation of the -OH of the carboxyl group), whereas at low pH conditions (pH < 2), it remains neutral. 14,21 Moreover, it was observed that the maximum load of ibuprofen molecules per dendrimer was realized when the drug was at its ionized state; that is, at a high pH environment. 14,21 Specifically, it was demonstrated 21 that for systems consisting of G3 PAMAM dendrimers, the maximum number of associated drug molecules per dendrimer did not exceed that of the primary amine groups of the dendrimer; that is, 32, regardless of the amount that was initially included in the solution.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the charging state of ibuprofen at different pH conditions, it has been found that at high pH conditions (pH > 10.5), ibuprofen becomes fully ionized (due to deprotonation of the -OH of the carboxyl group), whereas at low pH conditions (pH < 2), it remains neutral. 14,21 Moreover, it was observed that the maximum load of ibuprofen molecules per dendrimer was realized when the drug was at its ionized state; that is, at a high pH environment. 14,21 Specifically, it was demonstrated 21 that for systems consisting of G3 PAMAM dendrimers, the maximum number of associated drug molecules per dendrimer did not exceed that of the primary amine groups of the dendrimer; that is, 32, regardless of the amount that was initially included in the solution.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…14,21 Moreover, it was observed that the maximum load of ibuprofen molecules per dendrimer was realized when the drug was at its ionized state; that is, at a high pH environment. 14,21 Specifically, it was demonstrated 21 that for systems consisting of G3 PAMAM dendrimers, the maximum number of associated drug molecules per dendrimer did not exceed that of the primary amine groups of the dendrimer; that is, 32, regardless of the amount that was initially included in the solution. Taking into account the above experimentally available information, we have constructed models consisting of a G3 PAMAM dendrimer in different protonation states, water, and 32 ibuprofen molecules, as described in Table 1.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] A dendrimer with n generations of monomers is denoted a Gn dendrimer. Dendrimers have numerous technological applications, for example, in the targeted delivery of drugs 6,7 and, in particular, anticancer agents, [8][9][10] in light-harvesting applications, 11 and also as a tool for the development of nonviral gene delivery. 12 In a dendrimer solution, the individual macromolecules feature different conformations due to fluctuations of the monomers.…”
Section: Introductionmentioning
confidence: 99%
“…A workshop is being planned as part of this initiative that will identify scientific issues for the development of pediatric formulations, new methods of drug delivery (eg, use of dendrimers and inhalation devices for drug delivery in young infants, [37][38][39] economic barriers, research on taste and flavor preferences in infants and children, and methods to facilitate the development and approval of pediatric formulations.…”
Section: Future and Ongoing Activitiesmentioning
confidence: 99%